Right Mini-Thoracotomy Subaortic Membrane Resection. Issue 6 (November 2018) - Johnson, Carl A.; Siordia, Juan A.; Robinson, Davida A.; Sagebin, Fabio; Knight, Peter A.
Objective: Subaortic membrane is an anatomical intracardiac anomaly that may cause discrete subaortic stenosis and aortic insufficiency. Patients requiring subaortic membrane resection may benefit from a minimally invasive approach; however, subaortic membranes are typically resected through a median sternotomy. We present our initial clinical experience of adult patients who have undergone a mini-thoracotomy subaortic membrane resection. Methods: Eight patients who underwent an elective subaortic membrane resection performed through a mini-thoracotomy were retrospectively reviewed. A 5-cm mini-thoracotomy incision was made in the 2nd intercostal space; a videoscope was inserted through a separate incision within the same interspace. Cardiopulmonary bypass (CPB) was instituted via central arterial and peripheral venous cannulation and an aortotomy was made. The subaortic membrane was resected with shafted instruments. The left ventricular outflow tract was inspected and CPB was weaned. Thirty-day mortality, intensive care and hospital length of stay, ventilation time, operative times, postoperative morbidity, and need for additional procedures were evaluated. Results: The median CPB and cross-clamp times were 60 and 42 minutes, respectively. The median time to extubation was 3.6 hours. The median intensive care unit and hospital stay were 22 hours and 3 days, respectively. The postoperative left ventricular outflow tract mean gradients decreased significantly (26.5 vs. 9.4 mm Hg, P = 0.001). There were no conversions to sternotomy, perioperative strokes, or 30-day mortality. Conclusions: Subaortic membranes can be resected through a mini-thoracotomy approach with excellent clinical results.